Nonlinearity and the Study of Organizations - Piehl, DeWayne (Academy of Management Journal, 1974)
The article looks at a study which explores organizational behavior for nonlinear relationships. The use of linear theories and statistics within research design is discussed. Examples of nonlinarity are given. Graphs displaying nonlinear relationships are presented. Correlations between the proportion of time spent on technical work and the level of performance are considered. The author notes the need for adequate supervision to meet productivity standards. It is concluded that the benefits of exploring nonlinear relationships justify the associated costs.